A Search for Supernova Light Echoes in NGC 6946 with SITELLE - Radica, Michael (My University, 2019)
Scattered light echoes provide a unique way to engage in late-time study of supernovae. Formed when light from a supernova scatters off of nearby dust, and arrives at Earth long after the supernova has initially faded from the sky, light echoes can be used to study the precursor supernova through both photometric and spectroscopic methods. The detection rate of light echoes, especially from Type II supernovae, is not well understood, and large scale searches are confounded by uncertainties in supernova ages and peak luminosities. We provide a novel spectroscopic search method for detecting light echoes, and test it with 4 hours of observations of NGC 6946 using the SITELLE Imaging Fourier Transform Spectrometer mounted on the Canada-France-Hawaii Telescope. Our procedure relies on fitting a sloped model to continuum emission, and identifying negatively-sloped continua with the downslope of the emission component of a highly-broadened P-Cygni profile in the H$\alpha$ line, characteristic of supernova ejecta. We find no clear evidence for light echoes from any of the ten known Type II supernovae in NGC 6946, and only one light echo candidate from potential historical supernovae predating 1917. We do however, present an upper limit in H$\alpha$ brightness of \SI{5e-17}{erg/s/cm^2/arcsec^2} for light echoes within this galaxy. We discuss extensions of our methodology, as well as viability of this type of study in other objects, and with other instruments.
Keywords: Supernova Light Echoes